Protein phosphatase 1 abrogates IRF7‐mediated type I IFN response in antiviral immunity. Issue 10 (29th August 2016) - Wang, Ling; Zhao, Juan; Ren, Junping; Hall, Kenton H.; Moorman, Jonathan P.; Yao, Zhi Q.; Ning, Shunbin
Abstract : PP1 abrogates IRF7‐mediated type I IFN response in antiviral immunity . IRF7 is phosphorylated by IKKs or IRAK1 downstream of TLR signaling pathways in response to viral infection. PP1 targets IRF7 for dephosphorylation and attenuates type I IFN production in these signaling pathways. In addition, PP1 promotes IL6 production . Abstract : Interferon (IFN) regulatory factor 7 (IRF7) plays a key role in the production of IFN‐α in response to viral infection, and phosphorylation at IRF7 C‐terminal serine sites is prelude to its function. However, phosphatases that negatively regulate IRF7 phosphorylation and activity have not been reported. In this study, we have identified a conserved protein phosphatase 1 (PP1)‐binding motif in human and mouse IRF7 proteins, and shown that PP1 physically interacts with IRF7. Exogenous expression of PP1 subunits (PP1α, β, or γ) ablates IKKε‐stimulated IRF7 phosphorylation and dramatically attenuates IRF7 transcriptional activity. Inhibition of PP1 activity significantly increases IRF7 phosphorylation and IRF7‐mediated IFN‐α production in response to Newcastle disease virus (NDV) infection or Toll‐like receptor 7 (TLR7) challenge, leading to impaired viral replication. In addition, IFN treatment, TLR challenges and viral infection induce PP1 expression. Our findings disclose for the first time a pivotal role for PP1 in impeding IRF7‐mediated IFN‐α production in host immune responses.